Case report: Cerebral syphilitic gumma: a case retrospective report of eight cases - Liu, Jun; Zhang, Wenjun; Jiang, Qiuhua; Huang, Qianliang; Ye, Xinyun (Frontiers in Medicine, 2024)
Cerebral syphilitic gumma (CSG), a rare manifestation of neurosyphilis, presents characteristics akin to intracranial tumors, often leading to clinical misdiagnosis.This study aimed to summarize the clinical experience in diagnosing and treating CSG.The present study conducted a retrospective analysis of clinical data, encompassing the baseline characteristics, clinical presentation, diagnosis, treatment, and prognosis of eight patients with CSG who were treated and diagnosed by our institution.The median age at the initial diagnosis was 57.5 years, comprising six males and two females. The predominant clinical manifestations included headaches in eight cases, motor and sensory disorders in four cases, epileptic seizures in one case, and dysarthria in one patient. The serum treponema pallidum haemagglutination assay (TPHA) and toluidine red unheated serum test (TRUST) yielded positive in all eight patients. The contrast-enhanced magnetic resonance imaging (MRI) revealed irregular ring-shaped enhancement of lesions in three patients, while nodular enhancement of lesions was observed in five patients. In terms of treatment, seven patients underwent surgery. The postoperative pathological tissue showed granulomatous inflammation. Six patients exhibited an elevated protein concentration in their cerebrospinal fluid (CSF), while two patients demonstrated a reduced CSF glucose level. Additionally, positive results were obtained for both CSF TPHA and TRUST in all eight patients. The clinical diagnosis of CSG was confirmed in eight patients who exhibited notable clinical improvement following penicillin treatment. Subsequent reevaluation of the imaging findings demonstrated complete resolution of the enhanced lesions.In clinical practice, CSG should be considered for patients with intracranial lesions and positive serum syphilis antibodies. Timely and accurate diagnosis enables patients with CSG to achieve a more favorable prognosis through active anti-syphilis treatment.